Biomaterials and nanomedicine for bone regeneration: Progress and future prospects. Issue 2 (30th October 2021) - Zhou, Jun; Zhang, Zhongyang; Joseph, John; Zhang, Xingcai; Ferdows, Bijan Emiliano; Patel, Dylan Neal; Chen, Wei; Banfi, Giuseppe; Molinaro, Roberto; Cosco, Donato; Kong, Na; Joshi, Nitin; et al.
Abstract: Bone defects pose a heavy burden on patients, orthopedic surgeons, and public health resources. Various pathological conditions cause bone defects including trauma, tumors, inflammation, osteoporosis, and so forth. Auto‐ and allograft transplantation have been developed as the most commonly used clinic treatment methods, among which autologous bone grafts are the golden standard. Yet the repair of bone defects, especially large‐volume defects in the geriatric population or those complicated with systemic disease, is still a challenge for regenerative medicine from the clinical perspective. The fast development of biomaterials and nanomedicine favors the emergence and promotion of efficient bone regeneration therapies. In this review, we briefly summarize the progress of novel biomaterial and nanomedical approaches to bone regeneration and then discuss the current challenges that still hinder their clinical applications in treating bone defects. Abstract : We present an overview of common causes of bone defects, the unmet clinical needs, and the utility of biomaterials and nanotechnology to facilitate bone regeneration. Besides, we propose several key approaches to improve bone repair strategies. This perspective provides a guidance for future research direction of bone repair to improve treatment efficiency in both clinical and research perspectives.